Single-stage DNA splicing system via Yusof-Goode approach - Wen Li, Lim (2015)
Yusof-Goode (Y-G) rule is the new translucent way representing the rule in splicing system under the framework of formal language theory. The motivation behind using the Y-G approach is to simulate the actual recombinant behaviours of deoxyribonucleic acid (DNA) molecules. The current laboratory experimental approaches to obtain the product of the DNA splicing process involve time and cost with high probability of not getting the desired results. Hence, in this research, a mathematical concept of single-stage splicing language restricted to at most two non-palindromic initial strings and two rules with one recognition site is introduced via Y-G model. In addition, the characteristics of rule are investigated by providing mathematical proofs. Based on the characteristics of rule, some theorems and lemmas have been formulated to predict the number types of single-stage splicing language of Y-G splicing system. Furthermore, in order to determine the characterizations of single-stage splicing language, a model is developed via limit adjacency matrix approach. The limit adjacency matrix can also be used to predict the number types of transient, inert persistent and active persistent limit language. Finally, a graphic user interface and a computational model of single-stage limit language are developed using Microsoft Visual Basic (VB) programming code focusing on prediction of the conceivable resulted molecules, the number types of single-stage splicing language as well as the behaviours of single-stage splicing language